Electrochemical Gas Sensors: Free‐Standing Functionalized Graphene Oxide Solid Electrolytes in Electrochemical Gas Sensors (Adv. Funct. Mater. 11/2016). (14th March 2016) - Jiang, Gaopeng; Goledzinowski, Maciej; Comeau, Felix J. E.; Zarrin, Hadis; Lui, Gregory; Lenos, Jared; Veileux, Alicia; Liu, Guihua; Zhang, Jing; Hemmati, Sahar; Qiao, Jinli; Chen, Zhongwei
Abstract : Z. Chen and co‐workers develop an electrochemical gas sensor equipping a free‐standing sulfonic acid functionalized graphene oxide film as solid electrolyte, as described on page 1729. This sensor detects alcohol vapor in the environment, with excellent response, linearity, sensitivity, and selectivity perfomance. The design is not only suitable for portable breath analyzers, but also opens an alternative pathway to investigate the application of graphene derivatives in the field of gas sensors.